Empathy Is Not Enough: The Inhibiting Effects of Rape Myth Acceptance on the Relation Between Empathy and Bystander Intervention - Leone, Ruschelle M. (Journal of interpersonal violence, 2021)
Many bystander training programs aim to build empathy and decrease false and often prejudicial beliefs about rape and its occurrence (i.e., rape myth acceptance) to encourage prosocial bystander intervention. However, little empirical research has examined the association between these constructs. The aim of the present study was to examine the effect of rape myth acceptance on the relation between both (a) the ability to experience and share the emotions of others (i.e., emotional empathy) and (b) the ability to understand the emotions of others (i.e., cognitive empathy), and bystander decision-making and intentions to intervention. In Study 1, 154 undergraduate men completed measures of empathy, rape myth acceptance, and bystander decision-making. Findings demonstrated that emotional empathy was associated with more perceived pros for intervention among men with low, but not high, levels of rape myth acceptance. In Study 2, 185 undergraduate men and 210 undergraduate women completed similar measures as in Study 1, with the addition of a measure on bystander intentions to intervene. Results detected a conditional indirect effect of emotional and cognitive empathy on bystander intentions to intervene via the perception that there are more pros than cons to intervention. Findings suggest that empathic individuals may weigh helping a potential victim (i.e., pro) over hurting their own self-image (i.e., con). However, this process is inhibited among men who endorse greater rape myths, likely because they are inhibited from intervening at various steps of the decision-making model. Collectively, these results highlight the importance of targeting both empathy and rape myth acceptance to encourage prosocial bystander intervention.